Sistem Pendukung Keputusan dalam Menentukan Jurusan Siswa di Sekolah Menengah menggunakan Metode Fuzzy Tahani - Lubis, Alvin Sany; Sriani, Sriani (Universitas Hamzanwadi, 2025)
The major selection process at MAS Plus Al Ulum, Medan, is still conducted manually, making it prone to subjectivity, time-consuming, and potentially misaligned with students’ potential. Our research aims to develop a web-based decision support system for major recommendations using the Fuzzy Tahani method. This development research follows the Waterfall model, encompassing requirements analysis, design, implementation, and testing. Requirements were gathered through observation and interviews, followed by designing data processing logic and implementing a web-based system. Testing was performed using the black-box method on features such as login, homepage, student data input, fuzzification process, recommendation results, front page, dark mode, and logout. The analysis technique employed fuzzification and fuzzy queries to calculate students’ suitability for Science, Social Studies, or Religious Studies based on academic scores, interests, talents, and learning styles. The study involved 151 tenth-grade students. The resulting system automatically recommends Science, Social Studies, or Religious Studies based on the aforementioned criteria. Analysis of the 151 students’ data showed 72 students suited for Social Studies, 40 for Science, and 39 for Religious Studies. Testing confirmed all features functioned correctly without errors. This research provides a foundation for schools to create a more targeted, time-efficient, and student-aligned major selection strategy.